Synthesis and optical properties of CeO2 nanocrystalline films grown by pulsed electron beam deposition - Tatar, B.; Sam, E. D.; Kutlu, K.; Uergen, M. (SPRINGER, 2008)
The nanocrystalline cerium dioxide (CeO2) thin films were deposited on soda lime (SLG) and Corning glass by pulsed e-beam deposition (PED) method at room temperature. The structure of the produced CeO2 thin films was investigated by X-ray diffraction (XRD) analysis, X-ray photoelectron spectroscopy (XPS), and micro Raman spectroscopy. The surface topography of the films was examined by atomic force microscopy (AFM). Film thickness and growth morphologies were determined with FEG-SEM from the fracture cross sections. XPS studies gave a film composition composed of +4 and +3 valent cerium typical to nanocrystalline ceria structures deficient in oxygen. The ceria films were polycrystalline in nature with a lattice parameter (a) of 0.542 nm. The Raman characteristics of the source material and the films deposited were very similar in character. Raman lines for thin film and bulk CeO2 was observed at 465 cm(-1). The optical properties of the CeO2 films were deduced from reflectance and transmittance measurements at room temperature. From the optical model, the refractive index was determined as 1.8-2.7 in the photon energy interval from 3.5 to 1.25 eV. The optical indirect band gap (E-g) of CeO2 nanocrystalline films was calculated as 2.58 eV.
Keywords: STRUCTURAL-PROPERTIES; MICROSTRUCTURE; IRRADIATION; PRECURSORS; GLASSES; OXIDE; Materials Science